Pengaruh Tingkat Pengangguran terbuka dan Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan di Kota Malang - Alvina Damayanti; ladi fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2022)
Reducing poverty is main indicator in the success of economic development. The effectiveness of poverty alleviation is a leading factor in determining development strategies. Poverty is described as the most complex and difficult basic social problem, which until now continues to receive attention from the government. The purpose of the research is to see the impact of the open unemployment rate and population growth on the poverty rate in the Malang City Region. This study takes quantitative as a research method. Using secondary data based on data from the Central Statistics Agency of Malang City. Using time series data from 2011 – 2020. Through multiple regression analysis, it is shown that the open unemployment rate and population growth have a significant effect on the poverty rate. The level of open unemployment and the total population have a simultaneous impact on poverty. The partial increase in open unemployment has no significant impact on the poverty rate. Meanwhile, population growth partially has a significant effect on the value of the poverty level in Malang City.